Analisa Kuantitas dan Komposisi Timbulan Sampah Makanan Supermarket di Surabaya - Nakita Andara Maharani; Naniek Ratni Juliardi A.R.; Aussie Amalia; Aulia Ulfah Farahdiba (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
One of the serious problems being faced by several countries is food waste. The percentage of food waste generated in Indonesia in the last 20 years has tended to increase. In 2000, food waste generation in Indonesia was 39%, while in 2019 it increased to 55%. And 44% of food waste is food that is still suitable for consumption. There are various factors that can affect the amount of food waste generation. One of them is food waste behavior or someone's behavior towards food waste. In this study, researchers will analyze the quantity and composition of waste and also packaging type of waste generation from a supermarket located in Surabaya, East Java. As for this research, it used a survey collection technique in the form of secondary data, namely data collected by researchers from one of the supermarkets in Surabaya. Secondary data on waste composition and generation obtained are Oily fruits/seeds (peanuts, green beans, and coconut), Grains (wheat, rice, corn, wheat flour), Vegetables, Meat (beef, goat, chicken, pork), fish, milk, eggs, starchy foods, sugar, oil and fat. From the data that has been obtained, it is known that the generation of food waste at the Supermarket X is 40.8 kg per day with the dominating composition of waste consisting of vegetables, fruit and meat.